2021
DOI: 10.1155/2021/7872406
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Potential of Selected Medicinal Herbs and Their Isolated Natural Products

Abstract: Viruses are responsible for a variety of human pathogenesis. Owing to the enhancement of the world population, global travel, and rapid urbanization, and infectious outbreaks, a critical threat has been generated to public health, as preventive vaccines and antiviral therapy are not available. Herbal medicines and refined natural products have resources for the development of novel antiviral drugs. These natural agents have shed light on preventive vaccine development and antiviral therapies. This review inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 99 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…These results indicate that the highly oxygenated bisabolene sesquiterpenoid glycoside phyllaemblicins compounds found in Amla have potential against the Hepatitis B virus ( Lv et al, 2015 ). The compound glochicoccinoside D which was also obtained from Amla has antiviral potential against influenza A virus strain H3N2 and hand, foot, mouth virus (enterovirus) EV71 ( Perera et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the highly oxygenated bisabolene sesquiterpenoid glycoside phyllaemblicins compounds found in Amla have potential against the Hepatitis B virus ( Lv et al, 2015 ). The compound glochicoccinoside D which was also obtained from Amla has antiviral potential against influenza A virus strain H3N2 and hand, foot, mouth virus (enterovirus) EV71 ( Perera et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…PEF not only regulates immunity to reduce the risk of infection, but also directly fights against a variety of human pathogenic viruses. 113 Human papillomavirus (HPV) can cause the aberrant proliferation of squamous epithelium in human skin and mucous membranes. According to a survey, 114 high-risk HPV-16 infection is the most common cause of oral cancer in patients who have never used tobacco.…”
Section: Oral Cancermentioning
confidence: 99%
“…Therefore, their antiviral effects can be developed in the future [5,[17][18][19]. Arbab et al [20] identified and evaluated the antiviral activity of 60 plant species, concluding that the compounds contained in P. niruri L. and P. urinaria L. were active as HBV inhibitor agents [21]. Meanwhile, pure compounds from the Meniran plant were reported to inhibit the replication and expression of HBV in cells used as test models [4,[22][23][24][25][26] and were hepatoprotective [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%